1989
DOI: 10.1111/j.1440-1681.1989.tb02993.x
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Baroreceptor Resetting: Contributions of Chronic and Acute Processes

Abstract: I . Pressure threshold (Pth) and suprathreshold pressure sensitivity (Sth) are important measures of the pressure-discharge characteristics of arterial baroreceptors. An in vitro preparation of the rat aortic arch-aortic nerve has been used to assess the influence of extracellular ion concentration, distensibility, smooth muscle activation and rapid resetting on single fibre baroreceptor discharge.2. Changes in extracellular cations alter Pth and Sth in a reciprocal manner, suggesting that these two properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 21 publications
1
47
0
2
Order By: Relevance
“…In spontaneously hypertensive rats (SHR), resetting of the baroreceptor with depressed sensitivity is observed. 2 We have demonstrated that exercise training improves both the depressed baroreflex control of heart rate and reduces the level of arterial hypertension in SHR. After a 12-week period of low-intensity exercise training, the baroreflex sensitivity to bradycardia and tachycardia returned to near-normal values.…”
mentioning
confidence: 90%
“…In spontaneously hypertensive rats (SHR), resetting of the baroreceptor with depressed sensitivity is observed. 2 We have demonstrated that exercise training improves both the depressed baroreflex control of heart rate and reduces the level of arterial hypertension in SHR. After a 12-week period of low-intensity exercise training, the baroreflex sensitivity to bradycardia and tachycardia returned to near-normal values.…”
mentioning
confidence: 90%
“…1, inset). Since baroreceptors are actually activated by vessel wall stretch (Andresen & Yang, 1989 b), we also monitored the relation between aortic diameter and baroreceptor discharge (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…First, changes in smooth muscle tension, and therefore aortic diameter, evoke selective changes in threshold and therefore manifest themselves as parallel shifts of the pressure-response curve with no changes in threshold discharge frequency, suprathreshold gain, or maximal discharge rates . Second, changes in conditioning pressure (or diameter) selectively affect threshold and no other parameter of the discharge-response curve (Andresen & Yang, 1989 b). The mechanisms responsible for both rapid resetting and for smooth muscle modulation of baroreceptors are unknown, but they may be related .…”
Section: Discussionmentioning
confidence: 99%
“…10 In chronic hypertension, baroreceptor responsiveness to pressure is decreased: pressure threshold is increased and gain is decreased. These are the classic hallmarks of chronic hypertensive baroreceptor resetting.…”
Section: Rapid Resettingmentioning
confidence: 99%
“…4 Chronic adjustments in baroreceptor threshold and sensitivity occur during development, aging, and hypertension. 7 - 9 However, since rapid resetting is a quantitatively important determinant of baroreceptor threshold, 10 differences in the short-term adaptability of DS rat baroreceptors might contribute to the measured differences in baroreceptor properties. Although the mechanism of rapid resetting is not known, recent studies suggest that characteristics of Received June 25, 1990; accepted in revised form November 9, 1990. the baroreceptor itself and not vessel wall mechanical properties might be responsible.…”
mentioning
confidence: 99%